Parenting Styles, Social Network and Socio-Demographic Factors on Deviant Behavior among In-School Adolescents - Ehondor, Esohe Grace; Idris, Farouk Ige; Uye, Emmanuel Etim (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2024)
Deviant behaviors among in-school adolescents have been on the increased over the years. Studies that have examined different predictors of deviant behaviors have produced varied results. Therefore, this study examines parenting styles, social network, age and gender as predictors of deviant behavior among in-school adolescents in Ibadan South-west Local Government Area (LGA). Cross-sectional survey design was adopted while simple random sampling technique was used to select five public secondary schools in the LGA. Data were collected from 200 in-school adolescents using validated scales and analyzed using multiple regression and independent samples t-test to test two hypotheses. The result showed that parenting styles and social network jointly predicted deviant behavior among in-school adolescents (R2 = .05, F (2, 194) = 4.89, p .05). Also, the result revealed that age and gender jointly predicted deviant behavior [R2 = .10, F( 5,195) = 2.13, p .05]. Finally, both age (β = -.14, p .05) and gender (β =.17, p .05) independently predicted deviant behavior. The study concluded that parenting styles, social network, age and gender are excellent predictors of deviant behavior among in-school adolescents. The study recommended parents, school counselors and other stakeholders should provide good examples for adolescentsagainst deviant behaviors